SELF CONCEPT IN ENGLISH LEARNING - Muhammad, Abduh (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2017)
This paper is aimed at describing self concept in English learning.Â  This will explore the concept of self concept and its importance for students in learning English. Self concept is one of way for students toÂ  creatively in learning English. As a foreign language, English is not easy to learning by the students at the beginning of the study. For them, English is likely to be one difficulty in learning. The basic skills in English is the ability that requires the process of communicative competence, pronunciation, intonation, grammar and vocabulary improving. For the beginner is difficult to try. Naturally, they feel confused on the rule, like: grammar, vocabulary, pronunciation, and fluency. Some of students are afraid to be active in English. This phenomenon makes many students have low scores in English. The lessons must be relaxed and comfortable. So, by their self concept, the students will feel confident, they will not need to try hard to learn language. It will just come naturally and easily.